THE RHETORIC AND COMPONENTS OF LOVE IN THE LYRICS OF A JAPANESE SONG ABOUT LOVE BY MAJIKO - Indah Pertiwi Rahmadanti; Diana Kartika; Syahrial; Irma (Hikari: Jurnal Bahasa dan Kebudayaan, 2023)
Rhetoric can be defined as the art of using impressive words both orally and in writing. Rhetoric is usually created from the expression of thoughts and feelings through language that specifically shows the soul and personality of the writer. This study aims to explain the use of rhetoric and the components of love contained in the lyrics of a Japanese song about love by Majiko. The research method used is descriptive. The results of the research are rhetoric as follows: rhetoric of meaning, namely metaphor, simile, personification, hyperbole, oxymiron and rhetorical questions. Form Rhetoric namely Repetition, Parenthesis and Reticence. In each data found components of love namely intimacy, passion and commitment.